EXPLORING RESEARCH METHODOLOGIES QUALITATIVE IN HIGHER EDUCATION: STRATEGIES AND APPROACHES FOR ACADEMIC INQUIRY - Sariman; Eko Haryono; Muhamad Wahyudin; Faiz Zainal Muttaqin (https://www.ejournal.smaamc.sch.id/index.php/belajar, 2024)
Higher education is a forum for producing scientific innovations through the results of its research. The approach used in this research is a descriptive qualitative approach through literature studies, with sources from various books, articles, websites and other sources. The results of this research are: Understanding qualitative research methodology in higher education must be carried out comprehensively, understanding the meaning and techniques in carrying out research. Qualitative research methods in higher education include 1). The type of approach used by researchers, 2). Source -Data source, 3). Instruments and data collection, 4). Qualitative data analysis, 5). Data validity checking techniques. So that recommendations from the results of this research can be used for scientific research and development, educational innovation in universities and others, writing scientific articles and scientific and technological validation in general.